Character of Industrial 4.0 Skilled Workers - A, Ana; Meirawan, Danny; Dwiyanti, Vina; S, Saripudin (International Journal of Engineering and Technology, 2018)
Character of industrial 4.0 skilled worker is an important thing to prepare as soon to face industrial challenge in 4th revolution industry. Industrial 4.0 is an industry that combines automation technology with cyber technology. It will give more impact and change everything totally. Various forms of education must be introduced, but it still does not solve problems for older workers and do not want to change following the development of industrial progress. Because in industrial 4.0 of disruption era will be ordered robot as an effective and efficiency solution for industry and less cost also. So, as worker we must improve our skill to compete and win it. In this research contains three main topics are (a) knowing the industrial Era 4.0, (b) disruption in the industrial Era 4.0 (c) Skills to face industry 4.0. This research method use literature review as 1) searching and selection 2) describe, 3) analysis. The conclusions overall suggest that all workers must improve their skills to face industrial 4.0 era. In this research suggest 4 main skills are effective communication, learn and innovative, information-media-technology, skills full in life and career.Â Â